The importance of promoting self-reflection in the pedagogical practice of teachers - Víquez Fernández, Stephanie (2021)
Teaching is not an easy task because teachers have many and different roles in the class. Part of these roles is to self-reflect about their teaching practice to improve as a teacher and with this to help students to succeed. Some aspects may improve the process of self-reflection. This is crucial for personal growth since teachers can recognize their strengths and weaknesses by the observations and analysis of themselves. The different models of self-reflection will allow the teachers to be guided during the process of reflection. Moreover, these processes have almost the same stages: awareness of the need for self-reflection, the feelings, evaluation of the experiences, analysis of situations, conclusions, and action plans. The diverse strategies that may help to self-reflect on your own teaching practice are going to be explained in order to demonstrate that there are different ways to self-reflect and teachers need to select the one better fits for them. Therefore, self-reflection makes people more conscious about what needs to be changed or modified when teaching.